Personality resource mobilizing in psychological support service to athletes - Petrova, E. A.; Senkevich, L. V.; Jafar-Zade, D. A.; Romanova, A. V. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to rate benefits of the personality resource mobilizing and activation driven by productive coping strategies and life values and priorities to attain mental comfort in the psychological service to athletes. Sampled for the study were the 17-23 year old (n=100) academic athletes from a few Moscow universities. At the first stage of the study the sample was split up into Group 1 with high reported satisfaction rates, life values, optimism, activity and productive coping strategies; and Group 2 with relatively low satisfaction rates, life values, optimism, activity and coping strategies efficiency rates. At the second stage of the study, Group 2 was given individual and group psychological support service (two meetings per week) for 3 months. At the third and final stage, both of the groups were tested again to rate their progress. The pre- versus post-experimental tests showed significant (p<0.05) progress in many personality resource related aspects - both in the coping strategies productivity (alienation, decision-making) and life values and priorities (life goals, process, result, Self locus of control, Life locus of control, and overall satisfaction with life). The group activity and optimism and the total life satisfaction was tested to improve and, therefore, such counseling service model may be recommended to mobilize the personality resource, albeit further studies are needed to analyze the potential personality resource mobilization issues in the context of the modern sport psychology.